Africa Under The Prism : Contemporary African Photography from LagosPhoto Festival. - Ngozi Adichie, Chimananda; Nwagbogu, Azu (Ostfildern : Hatje Cantz, 2015)
Steketee, Anoek ; Sassen, Viviane ; Akintunde, Akinleye ; Balden, Cristina ; Osodi, George ; Pongo, Léonard ; Kurzen, Benedicte ; Willocq, Patrick
Fotofestival Lagos, 2010-2014, Lagos, Nigeria
boek